2011
DOI: 10.1097/jto.0b013e31820a0ec0
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Type of Epidermal Growth Factor Receptor Mutations in African Americans with Non-small Cell Lung Cancer

Abstract: Background Epidermal growth factor receptor (EGFR) mutations in non-small cell lung cancer predict response to tyrosine kinase inhibitors (TKIs). Mutations occur more commonly in never-smokers and East Asians but there are conflicting reports on the frequency of EGFR mutations in tumors from African Americans. Methods Tumors from 67 African American and 77 Caucasian participants in previous case-control studies of lung cancer were selected to determine EGFR mutational status. Mutation analysis was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 14 publications
4
54
1
Order By: Relevance
“…Most typically, in Asian studies, higher incidence of EGFR mutation in female gender has been demonstrated . Studies in the Western world have provided results similar to those reported in Asian investigations, and female gender was detected as one of the most important predictors of EGFR (Arrieta et al, 2011;Cote et al, 2011;Leary et al, 2012). Also in our study higher rates of EGFR mutation were found in the female gender in parallel with the literature data.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most typically, in Asian studies, higher incidence of EGFR mutation in female gender has been demonstrated . Studies in the Western world have provided results similar to those reported in Asian investigations, and female gender was detected as one of the most important predictors of EGFR (Arrieta et al, 2011;Cote et al, 2011;Leary et al, 2012). Also in our study higher rates of EGFR mutation were found in the female gender in parallel with the literature data.…”
Section: Discussionsupporting
confidence: 91%
“…For example, incidence of EGFR mutations was 19% in Argentina, and 67% in Peru (Arrieta et al, 2011). An investigation among African-Americans found a lower incidence (11%) of EGFR mutation (Cote et al, 2011). Similarly, a study conducted in the UK, its incidence was revealed as 11% (Leary et al, 2012).…”
Section: Discussionmentioning
confidence: 87%
“…A total of 4 African-Americans were included in the non-Asian group, as African-Americans have been reported to show similar frequencies of mEGFR and mKRAS to Caucasians (26)(27)(28), and it was confirmed that none of the 4 African-Americans harbored mEGFR and that 2 harbored mKRAS. The mutations and CNGs in 12 Asian patients with lung adenocarcinomas whose DNA samples were obtained from Western countries were also determined.…”
Section: Discussionmentioning
confidence: 98%
“…COMMENT The frequency of the EGFR mutations in different populations is well documented. [16][17][18][19] For example, the mutation rate is higher in Asians and female nonsmokers. 20 However, the EGFR mutation rate in lung adenocarcinomas among the US Hispanic population has not been previously investigated to our knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of EGFR mutations is approximately 30% in Asian populations, 15% in whites, and 19% in African Americans. 16,17 However, data on the frequency of EGFR mutations in lung adenocarcinoma among Hispanics in the United States is not currently available, to our knowledge. Of note, the frequency of EGFR mutations in non-small cell carcinoma of the lung has been reported to be 33.2% in Latin American countries overall, which is similar to the Asian population.…”
mentioning
confidence: 99%